Fostering student sense making in elementary science learning environments: Elementary teachers' use of science curriculum materials to promote explanation construction. Issue 8 (13th August 2013) - Zangori, Laura; Forbes, Cory T.; Biggers, Mandy
Abstract While research has shown that elementary (K‐5) students are capable of engaging in the scientific practice of explanation construction, commonly‐used elementary science curriculum materials may not always afford them opportunities to do so. As a result, elementary teachers must often adapt their science curriculum materials to better support students' explanation construction and foster student sense making. However, little research has been conducted to explore if and, if so, how and why, elementary teachers modify science curriculum materials to engage students in explanation construction. We use an embedded mixed methods research design to explore elementary teachers' (n = 45) curricular adaptations and pedagogical reasoning. We collected and quantitatively analyzed a matched set of 121 elementary science lesson plans and video recorded lesson enactments to investigate the extent to which inservice elementary teachers engage in instruction to more productively support students' explanation construction. Our findings suggest that the curriculum materials heavily emphasized hands‐on engagement and data collection over explanation construction and that the teachers' adaptations did not fundamentally alter scientific sense‐making opportunities afforded students in the lesson plans. Interviews and other artifacts were also collected and analyzed to construct a multiple‐case study of four of these elementary teachers. Findings from the case study suggest that the teachers' conceptions of explanation construction and concerns about the abilities of their students to engage in scientific explanations impacted their curricular adaptations. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50: 989–1017, 2013